2022
DOI: 10.3390/ijerph192214727
|View full text |Cite
|
Sign up to set email alerts
|

Public Health System Economic Efficiency and COVID-19 Resilience: Frontier DEA Analysis

Abstract: The article summarizes the arguments and counterarguments in the scholarly discussion about the problem of choosing a model of healthcare organization. The study’s primary goal was to identify the economic efficiency of the public health system and resistance to COVID-19. The relevance of addressing this research issue is that the epidemiological challenges posed by the pandemic worldwide have manifested themselves differently in various countries. Therefore, it is advisable to consider the effectiveness of pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 42 publications
0
15
0
1
Order By: Relevance
“…Similarly, those nations who used the health care system model based on the concept of national insurance ranked second in terms of economic efficiency, with a level of 95.5%. Those nations who used the market model of health care system, in which the majority of money spent on medical services come from the population's own savings, had the lowest performance outcomes [30]. Total vaccination coverage in Ukraine indicated by WHO statistics were also low as compared to other countries in Europe showed poor and inefficiency of healthcare system of Ukraine [31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, those nations who used the health care system model based on the concept of national insurance ranked second in terms of economic efficiency, with a level of 95.5%. Those nations who used the market model of health care system, in which the majority of money spent on medical services come from the population's own savings, had the lowest performance outcomes [30]. Total vaccination coverage in Ukraine indicated by WHO statistics were also low as compared to other countries in Europe showed poor and inefficiency of healthcare system of Ukraine [31].…”
Section: Discussionmentioning
confidence: 99%
“…Germany, Austria, Belgium, the Czech Republic, France, the Netherlands, and Switzerland used the Bismarck model. Canada, Australia, Italy, and Thailand used the national insurance model, while China, India, and Portugal used the market model [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the complexity of their analysis may challenge result interpretation, particularly for policymakers not familiar with the method. In another study, Kuzior et al (2022) categorized healthcare systems and found the Beveridge model performed the best, followed by the Bismarck and National Insurance models, while the Market model demonstrated the poorest resilience to the pandemic. However, clarity was lacking on data collection duration and specific COVID-related variables employed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Ho (2015) used the prism of the impact of health insurance schemes on financing the needs of people in different countries. Spending on the public health system as a percentage of GDP can positively and negatively impact labor productivity and will depend on the specific nature of spending on the public health system (Kuzior et al, 2022a). On the one hand, increased spending on the public health system and access to new medical technologies improve health, increasing labor productivity (Horváth & Gyenge, 2023).…”
Section: The Impact Of Insurance On Labor Productivitymentioning
confidence: 99%